Correlation between arterial blood pressures and regional cerebral oxygen saturation in preterm neonates during postnatal transition-an observational study - Pfurtscheller, Daniel; Wolfsberger, Christina H.; Höller, Nina; Schwaberger, Bernhard; Mileder, Lukas; Baik-Schneditz, Nariae; Urlesberger, Berndt; Pichler, Gerhard (Frontiers in Pediatrics, 2022)
Objective To assess whether blood pressure (systolic (SABP), diastolic (DABP), and mean arterial blood pressure (MABP) and cerebral-regional-oxygen-saturation (crSO2) and cerebral-fractional-tissue-oxygen-extraction (cFTOE) are associated after immediate fetal-to-neonatal transition in preterm neonates with and without respiratory support. Study design Post-hoc analyses of secondary outcome parameters of prospective observational studies were performed. We included moderate and late preterm neonates with and without respiratory support with cerebral NIRS monitoring (INVOS 5100c) and an oscillometric blood pressure measurement at minute 15 after birth. Heart rate (HR) and arterial oxygen saturation (SpO2) were monitored routinely. Blood pressure values were correlated with crSO2 and cFTOE. Results 47 preterm neonates with NIRS measurements and blood pressure measurement during immediate transition after birth were included. Twenty-five preterm neonates (gestational age: 34.4±1.6 weeks) received respiratory support. In these neonates crSO2 correlated significantly positively with systolic blood pressure (SABP; r=0.46, p=0.021), diastolic blood pressure (DABP; r=0.51, p=0.009) and, mean arterial pressure (MABP; r=0.48, p=0.015). cFTOE correlated significantly negatively with SABP (r=-0.44, p=0.027), DABP (r=-0.49, p=0.013) and mean MABP (r=-0.44, p=0.029). Twenty-two preterm neonates (gestational age: 34.5±1.5 weeks) did not receive respiratory support. In those neonates, neither crSO2 nor cFTOE correlated with blood pressure. Conclusion In compromised moderate and late preterm neonates with respiratory support, both, crSO2 and cFTOE correlated with blood pressure. These findings suggest that passive pressure-dependent cerebral perfusion was present in preterm neonates with respiratory support, indicating an impaired cerebral autoregulation in those compromised preterm neonates.